ADJECTIVES-DEFINITION, FORMS, TYPES, USAGE AND EXAMPLES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
In this scientific article, the types, levels, definition of quality are given, several examples are given. That is, there is a lot of information about quality